Relative stability of linear systems - Jorge Sá Esteves (2008)
In this paper we analyze the evolution of the relative error in the state of linear systems subject to perturbations. For this purpose we introduce the property of relative stability. The relevance of this property is illustrated by means of a case study, namely the computation of the Erlang-B function, which is well-known in the context of Queueing Theory.